Effect of predators on the spread of Hantavirus infection - Yusof, F.M.; Md. Ismail, A.I.B.; Ali, N.M. (Universiti Kebangsaan Malaysia, 2014)
Hantavirus is a serious disease caused by rodents which can lead to mortality. Many efforts have been carried out by researchers to develop and analyze mathematical models of Hantavirus infection. In this paper, the Peixoto and Abramson (2006) biodiversity model is modified to include the effect of predators and study the prediction of the modified model. When rodent and predator populations are in competition, the predator populations have the effect of reducing the prevalence of infection. Predators may be used for control and reduces the number of competing species to stabilize the populations at a persistent equilibrium.